Study protocol to develop a patient-reported outcome measuring disability associated with unilateral vocal fold paralysis: a mixed-methods approach with the CoPE collaborative - David Schlundt; Sara Fernandes-Taylor; Cara Damico Smith; Natalia Arroyo; Kemberlee Bonnet; Margarete Wichmann; Irene Feurer; David O Francis (BMJ Open)
Introduction Patient-reported outcome (PRO) measures are increasingly developed with multisite, representative patient populations so that they can serve as a primary endpoint in clinical trials and longitudinal studies. Creating multisite infrastructure during PRO measure development can facilitate future comparative effectiveness trials. We describe our protocol to simultaneously develop a PRO measure and create a collaborative of tertiary care centres to address the needs of patients with unilateral vocal fold paralysis (UVFP). We describe the stakeholder engagement, information technology and regulatory foundations for PRO measure development and how the process enables plans for multisite trials comparing treatments for this largely iatrogenic condition.Methods and analysis The study has three phases: systematic review, measure development and measure validation. Systematic reviews and qualitative interviews (n=75) will inform the development of a conceptual framework. Qualitative interviews with patients with UVFP will characterise the lived experience of the condition. Candidate PRO measure items will be derived verbatim from patient interviews and refined using cognitive interviews and expert input. The PRO measure will be administered to a large, multisite cohort of adult patients with UVFP via the CoPE (vocal Cord Paralysis Experience) Collaborative. We will establish CoPE to facilitate measure development and to create preliminary infrastructure for future trials, including online data capture, stakeholder engagement, and the identification of barriers and facilitators to participation. Classical test theory psychometrics and grounded theory characterise our approach, and validation includes assessment of latent structure, reliability and validity.Ethics and dissemination Our study is approved by the University of Wisconsin Health Sciences Institutional Review Board. Findings from this project will be published in open-access journals and presented at international conferences. Subsequent use of the PRO measure will include comparative effectiveness trials of treatments for UVFP at CoPE Collaborative sites.